The osteogenic effects of swimming on bone mass, strength, and microarchitecture in rats with unloading-induced bone loss - Volpon, Jose Batista; Silva, Adriana Valadares; Falcai, Mauricio Jose; Louzada, Mario Jefferson Quirino; Zamarioli, Ariane; Kotake, Bruna Gabriela Dos Santos; Issa, João Paulo Mardegan (Wiley, 2015)
The effect of nonweight-bearing exercise on osteoporotic bones remains controversial and inconclusive. The purpose of this study was to evaluate the effects of swimming on osteoporotic tibias of rats submitted to hindlimb suspension. Initially, 20 Wistar rats were used to confirm a significant bone loss following 21 days of unloading. Thirty rats were then divided into 3 groups and followed during 51 days: CON (nonsuspended rats), S+WB (suspended rats for 21 days and then released for regular weight-bearing) and, S+Swim (suspended rats for 21 days and then released from suspension and submitted to swimming exercise). We observed that swimming exercise was effective at fully recovering the bone deterioration caused by suspension, with significant increments in BMD, bone strength and bone volume. On the other hand, regular weight-bearing failed at fully restoring the bone loss induced by unloading. These results indicate that swimming exercise may be a potential tool to improve bone density, strength, and trabecular volume in tibias with bone loss induced by mechanical unloading in suspended rats. We conclude that this modality of activity could be beneficial in improving bone mass, strength, and architecture in osteoporotic individuals induced by disuse, such as bed rest or those exposed to microgravity, who may not be able to perform weight-bearing exercises.
Keywords: Bone tissue; Hindlimb suspension; Nonweight-bearing exercise; Osteoporosis